2017
DOI: 10.1016/j.nicl.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between individual differences in functional connectivity and facial-emotion recognition abilities in adults with traumatic brain injury

Abstract: Although several studies have demonstrated that facial-affect recognition impairment is common following moderate-severe traumatic brain injury (TBI), and that there are diffuse alterations in large-scale functional brain networks in TBI populations, little is known about the relationship between the two. Here, in a sample of 26 participants with TBI and 20 healthy comparison participants (HC) we measured facial-affect recognition abilities and resting-state functional connectivity (rs-FC) using fMRI. We then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 68 publications
1
27
0
1
Order By: Relevance
“…Participants were recruited through the University of Iowa community and through the University of Iowa Brain Injury Registry (Rigon, Turkstra, et al, 2016; Rigon, Voss, Turkstra, Mutlu, & Duff, 2016, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…Participants were recruited through the University of Iowa community and through the University of Iowa Brain Injury Registry (Rigon, Turkstra, et al, 2016; Rigon, Voss, Turkstra, Mutlu, & Duff, 2016, 2017). …”
Section: Methodsmentioning
confidence: 99%
“…A line of research has begun to investigate the integrity of other well‐established large‐scale functional neural networks post‐TBI. In adults with moderate to severe TBI, abnormal functional connectivity (including both hypo‐ and hyper‐connectivity) has been observed in resting‐state networks subserving motor, memory, cognitive, and visual processing (Guo et al, ; Hillary et al, , ; Rigon, Duff, McAuley, Kramer, & Voss, ; Rigon, Voss, Turkstra, Mutlu, & Duff, , ; Shumskaya, van Gerven, Norris, Vos, & Kessels, ; Threlkeld et al, ). The most common findings points to functional connectivity abnormalities in the brain's default mode network (DMN) and salience network after adult TBI (Guo et al, ; Hillary et al, ; Threlkeld et al, ; Zhou et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Davis and colleagues suggested that prosopagnosia could be either developmental or acquired as a consequence of specific cortical neuronal damage (3,4). Overall, exploitation of super-recognizers is invaluable, particularly in lawenforcement and intelligence agencies (5)(6)(7)(8)(9).…”
Section: Discussionmentioning
confidence: 99%
“…These individuals are the exact opposite of people with a medical condition, known as "prosopagnosia" or "face blindness". In this condition, an individual has deteriorated or limited abilities to recognise faces (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%